Antimicrobial photodynamic therapy against oral biofilm: influencing factors, mechanisms, and combined actions with other strategies - Li, Yijun; Sun, Guanwen; Xie, Jingchan; Xiao, Suli; Lin, Chen (Frontiers in Microbiology, 2023)
Oral biofilms are a prominent cause of a wide variety of oral infectious diseases which are still considered as growing public health problems worldwide. Oral biofilms harbor specific virulence factors that would aggravate the infectious process and present resistance to some traditional therapies. Antimicrobial photodynamic therapy (aPDT) has been proposed as a potential approach to eliminate oral biofilms via in situ-generated reactive oxygen species. Although numerous types of research have investigated the effectiveness of aPDT, few review articles have listed the antimicrobial mechanisms of aPDT on oral biofilms and new methods to improve the efficiency of aPDT. The review aims to summarize the virulence factors of oral biofilms, the progress of aPDT in various oral biofilm elimination, the mechanism mediated by aPDT, and combinatorial approaches of aPDT with other traditional agents.